Flat panel CT following stapes prosthesis insertion: an experimental and clinical study - Plath, Karim (European radiology, 2012)
ObjectivesAnatomical information of the middle and inner ear is becoming increasingly important in post-operative evaluation especially after stapesplasty with unsuccessful improvement of the air-bone gap (ABG). So far computed tomography (CT) has been the first choice for detection of reasons for recurrent hearing loss. CT has the disadvantage of metal-induced artefacts after insertion of middle ear implants and of a relatively high irradiation dose.MethodsFlat panel CT (fpCT) was performed in three temporal bone specimen after experimental insertion of different stapes prostheses, aiming to validate the accuracy of fpCT of the middle and inner ear. Additionally, 28 consecutive patients, supplied with different stapes prostheses underwent post-operative fpCT to compare the pre- and post-operative hearing results with the determined prosthesis position in the middle and inner ear.ResultsIn all cases, fpCT showed a statistically significant correlation between hearing improvement and prosthesis position. This technique provided detailed post-operative information of the implant position in patients and temporal bone specimen.ConclusionsThe new imaging technique of fpCT allows the immediate and almost artefact-free evaluation of surgical results following stapesplasty. Further benefits are a lower irradiation dose and higher isovolumetric resolution compared with standard CT. Key Points • Flat panel computed tomography (fpCT) helps otosurgeons design precise stapes protheses • fpCT allows a prediction of the postoperative hearing outcome in patients • fpCT is an adequate imaging technique for immediate postoperative quality control. Postoperative management of patients with prosthesis-related complications is more appropriate